Correlation of maternal anemia during pregnancy and low birth weight infant at Chonburi Hospital - Sunaree Pitchaiprasert; Teera Siwadune (The Royal Thai College of Obstetricians and Gynaecologists, 2009)
Objective To examine the correlation between maternal anemia and low birth weight infant and other perinatal outcomes. Material and Method A retrospective 5,526 pregnant women was studied from Janury 1, 2004 to December 31, 2007 at Department of Obstetrics and Gynecology, Chonburi Hospital, Thailand. The study group consisted of 1,197 were anemia (hematocrit less than 33 % in first antenatal care and gave birth at Chonburi Hospital) and the control group consisted of 4,329 were non-anemia (hematocrit > 33 % in first ANC and gave birth at Chonburi Hospital). Demographic and perinatal outcomes (included low birth weight at delivery, preterm delivery, Apgar score at 1 and 5 min, mode of delivery, and hospitalization ) were collected and compared between the study and control groups. Data was analysed using descriptive statistics and presented as mean + SD and percentage. Statistical significance was using the Chi-square test and Fisher's Exact test for differences in qualitative variables and the Student t-test for differences in continuous variables. 95% confidence interval (CI) were computed. p-value less than 0.05 were considered statistically significant. Result The anemic pregnant women tended to be younger, lower body weight, late first antenatal care visit and have newborn large for gestational age. There was no correlation between maternal anemic status with low birth weight (9.4% , 11.1% ; p = 0.245) and birth asphyxia (3.4% , 3.7% ; p = 0.63) when compared with the control group. The anemic group had more sick newborn and fetal dead but the cesarean section, vacuum delivery and breech assisted delivery rate was lower than the control group. Conclusion No correlation was found between maternal anemia with low birth weight infant and birth asphyxia. Operative and assisted deliveries tended to be lower in the anemic pregnant women.